Peran Taman Baca Masyarakat (TBM) terhadap Peningkatan Budaya Literasi di Masyarakat Desa Titik, Kecamatan Semen, Kabupaten Kediri - Lailatul Azizah, Siti Nur; Silviana, Willia Arum; Setyorini, Zanuarsita; Faradiba, Anggita Ayu; Falantiano, Fachrul Eza; Sulistyowati, Sulistyowati (Welfare : Jurnal Pengabdian Masyarakat, 2024)
The interest and reading culture of Indonesian society is still very low. The government has made various efforts to overcome this problem. One of the government's efforts is through community reading parks (TBM). Community Reading Parks (TBM) play an important role in efforts to increase literacy culture in society, especially in areas with limited access to formal education resources. This research report is entitled "The Role of Community Reading Parks (TBM) in Increasing Literacy Culture in the Titik Village Community, Semen District, Kediri Regency”. This research aims to examine the role of TBM in improving society's literacy culture. The research method used is a qualitative approach, where data is collected through observation and in-depth interviews. This research activity was carried out at TBM Titik Pena. The research results show that the existence of TBM has a significant positive impact in increasing interest in reading, providing access to a variety of reading materials, and facilitating various literacy activities involving people from various circles. Apart from that, TBM also acts as an informal learning center that supports the development of residents' knowledge and skills. Supporting factors and implementation of TBM activities are adequate facilities, various kinds of reading books from early childhood to adulthood, support from the community, as well as donations of books to complement reading from donors. The inhibiting factors for TBM activities are children's boredom and laziness, as well as the various activities of managers and volunteers. This research emphasizes the importance of TBM support and development to strengthen literacy culture in Indonesia.